2018
DOI: 10.3389/feduc.2018.00073
|View full text |Cite|
|
Sign up to set email alerts
|

A Learning Community Approach for Post-Secondary Large Lecture Courses

Abstract: This design-based research (DBR) study examined the ways in which a learning community approach can be enacted in large undergraduate lecture courses through a scaffolded, complex curricular design that utilizes active and inquiry-based learning. By combining a traditional lecture with breakout tutorials, the study involved two iterations, firstly by adopting the Fostering Communities of Learners (FCL) pedagogical model, then by augmenting the model by blending its methodology with elements from a more recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The subject contents do not rest mainly on written materials and videos, but they are collaboratively completed in the weekly discussion forums in which both students and teachers participate. This active learning model also provides positive results in face-to-face courses ( Deslauriers et al , 2019 ; Ehrlick and Slotta, 2018 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 82%
“…The subject contents do not rest mainly on written materials and videos, but they are collaboratively completed in the weekly discussion forums in which both students and teachers participate. This active learning model also provides positive results in face-to-face courses ( Deslauriers et al , 2019 ; Ehrlick and Slotta, 2018 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 82%
“…As a consequence, we expect that openness should be important for both, students' well-being (Bardi et al, 2009), and level of adaptation to the student environment and academic requests. Although the creation of student communities influenced how other theoretical models study the learning communities, Ehrlick and Slotta (2018) believe that in the last two decades there was no significant progress either in theory, or in practice.…”
Section: Student Openness To Build Learning Communitiesmentioning
confidence: 99%
“…Research into the outcomes of learning communities has revealed that learning communities are powerful means for creating and sharing knowledge and can provide several benefits to both their individual members and the community as a whole. These benefits include improved student retention in academic courses (Kern & Kingsbury, 2019;Lei et al 2011), increased development of self-regulated learning strategies (Beishuizen, 2008), increased interaction and collaboration within the community (Buchenroth- Martin et al, 2017;Garrison, 2017), increased flow of information and knowledge sharing among community members Ehrlick & Slotta, 2018), increased sense of engagement and motivation (Nye, 2015;Pike et al, 2011;Rocconi, 2011), increased sense of belonging Masika & Jones, 2016), and relatedness to peers and teachers (Beachboard et al, 2011).…”
Section: Communities Of Learnersmentioning
confidence: 99%